The Effect of Disinfectants on the Properties of Dental Impression Materials - R. Vrbová; V. Fialová; P. Bradna; D. Houšová (Czech Dental Chamber, 2016)
Introduction: The disinfection of dental impressions is necessary in terms of preventing the transmission of infection from patients' blood or saliva before processing at a dental office or laboratory. The adverse effects of the disinfection process can result in dimensional changes of the dental impressions, a change in surface quality and loss of the ability to reproduce the details of hard and soft tissues in the oral cavity. All these potential negative effects can ultimately influence the final prosthetic work. Aim: This study aimed to assess "in vitro" the impact of several commercially available disinfectants on detail reproduction and the dimensional changes of dental impressions made from various types of dental impression materials and their compatibility with dental gypsums. Methods: In this study alginate (Ypeen, Alligat fast set, Elastic Cromo) and elastomer (Variotime Medium Flow, Xantropren L blue, Impregum Soft) dental impression materials in combination with four disinfectants (Aseptoprint Liquid, Zeta 7 solution, Silosept, Dentaclean Form ) and gypsums type 3 (Mramorit Blue) and type 4 (BegoStone plus) were tested. The methods were executed using technical standards ČSN EN 21563 Dental alginate impression materials and ČSN EN ISO 4823 Dental elastomeric impression materials. Detailed reproduction of the dental impressions, their dimensional changes and compatibility with gypsum were evaluated on the impressions of the metal block with lines of defined dimensions. Dimensional change was defined as the percentual change of the distance between lines reproduced on disinfected impressions and the lines of defined dimensions on the metal block. The results were statistically analysed using Statistica 12 software (StatSoft Inc., Tulsa, USA). Two-factor and one-factor analysis of variance ANOVA with Tukey HSD post-hoc tests at the significance level of 0,05 % were used. Results: The detail reproduction of dental impressions and their compatibility with gypsum worsened when the alginate impression materials were combined with disinfectant Dentaclean Form. The surface of other tested impression materials remained unchanged after disinfection, as were the reproduction of details and compatibility with gypsum. Dimensional changes after disinfection were the highest in alginate material Elastic Cromo and the shortest in polyether material Impregum Soft. Conclusion: The disinfection of dental impressions is currently a necessary step before further processing in dental laboratories. However, it was confirmed that the desired properties of impressions may be negatively affected by disinfectant, particularly in the case of alginate materials. It is therefore always important to approach the selection of specific disinfectant with respect to the manufacturer's recommendations and the available information regarding this issue.